Continuity in the «College-University» System in the Training of Future Primary School Teachers on the Basis of Praxeological Approach - Galina Dzhanda (Pedagogical Discourse, 2021)
The article considers the issue of continuity in the training of future primary school teachers on the basis of a praxeological approach in the "college-university" system. The main purpose of the study was chosen - to determine the possibilities of ensuring the continuity of learning in the conditions in this system. The task of this study was set: to analyze and specify the features of continuing education in the «college-university» system; identify the main ways to ensure the continuity of education in the system under study. To achieve the goal a set of methods was used: theoretical; empirical; methods of mathematical statistics. It is determined that the concept of «continuity» has been considered by many scholars from a psychological and pedagogical point of view. We have come to the conclusion that «continuity» should be understood as a regulator of a person's transition from one stage of his development to another, which ensures the strength of the connection of units of different levels. The works of scientists present a model of ensuring and achieving continuity in the level of education, which consists of: methodological foundations; theoretical foundations; creation of information environment; analysis of the continuity principles impact effectiveness; diagnosing continuity.In our experiment, we implemented the principle of continuity using the disciplines «Ukrainian language for professional purposes» (studied at the college) and "Methods of teaching language and literature education (Ukrainian language) (studied at the university). They fully provide a combination of new forms of organization and activities with the old ones. Taking into account the interdisciplinary connections allows to focus on the development of knowledge, skills and abilities not only on the previous stage of learning, but also on those knowledge, skills, abilities that are related to the unit of language studied in other sections of the course.Thus, the principle of continuity affects the readiness of college graduates for the educational process at the university. Its use ensures the formation of the professionalism of the future specialist.